"Walled city" in the tropics an analysis of the urban fabric and tropical design considerations of Intramuros. - Orbon, Glenn T. (2014)
The "walled city" of Intramuros in Manila was established by the Spaniards at the mouth of the Pasig River facing Manila Bay, serving as the center of government during the Spanish colonial period and a template for future urban cities in the archipelago. The regular grid layout of this area was based on Laws of the Indies and the model used despite the irregularity of its perimeter stone walls. This case study analyzes the tropical design considerations used by the Spaniards in the urban development of Intramuros.